The historical topography of Samarra - Northedge, Alastair, (Samarra studies ;, 2007)
The Historical Topography of Samarra sets out to explain the second capital of the Abbasid caliphs at Samarra, on the Tigris above Baghdad, in the period 836 to 892 AD, by an analysis of the archaeological site and the medieval Arabic texts which describe it. The volume defines for the first time the nature of city construction by the Abbasid caliphs, one of the world powers of the time, and the foundation of modern Iraq. It is the first of a series of Samarra Studies." -- BOOK JACKET.